Praktik Pengelolaan Keuangan di Kelurahan Tamallayang, Kecamatan Bontonompo - AMBARWATI AKIB; NURKHOLIFAH BURHANUDDIN; NURUL EMIL SAFITRI; NADYA ANNISA NASRUDDIN; ANDI NURUL TENRIWALI HASANUDDIN (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Household financial management is a crucial aspect in maintaining family economic stability; however, the level of financial literacy among the community, particularly housewives, remains relatively low. This condition leads to inadequate financial planning, lack of transaction recording, and low saving behavior. This community service activity aims to improve the knowledge and skills of housewives in managing household finances through simple and practical financial literacy practices in Tamallayang Village, Bontonompo District. The methods used include counseling, interactive discussions, budgeting practice, and evaluation through pre-test and post-test. The activity involved 20 participants from the local community. The results indicate a significant improvement in participants’ knowledge, with the “good” category increasing from 25% to 85% after the training. This demonstrates that contextual and practice-based learning methods are effective in enhancing financial literacy. Therefore, this program successfully encourages more disciplined and planned financial behavior, contributing to improved family welfare. It is recommended that similar programs be implemented sustainably and expanded to achieve a broader impact. Keywords.:financial literacy, financial management, housewives, community service, financial management practices